Pengolahan Pangan Jajanan Tradisional pada Kelompok Kusuma Dewi di Kabupaten Jembrana, Bali - I Putu Candra; Ni Made Ayu Suardani Singapurwa; Luh Suariani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The development of processing technology for the food industry produces more and more various processed products widely circulated in the market. In the context of empowering rural communities, namely by increasing knowledge, attitudes, skills, and behavior, it is necessary to develop a plan of activities and assistance according to the needs of the community. Traditional street food is one of the foods that must be preserved and maintained in each area to maintain local wisdom. This service activity was carried out at the Kusuma Dewi Women Farmers Group in Segah Hamlet, Asahduren Village, Pekutatan District, Jembrana Regency, Bali. quality. Partners do not understand entrepreneurial knowledge, so it is necessary to provide an understanding of the production and marketing of processed traditional snacks. The way to overcome the problems faced by partners is to actively and explore community participation, provide appropriate technology for processing traditional snacks; provide knowledge on good processing methods, processing hygiene and hygiene, product packaging and labeling, marketing, and entrepreneurship; provide bookkeeping knowledge, and provide equipment assistance. The results of this activity are the use of appropriate technology in processing traditional snacks, understanding the application of processing methods and good sanitation conditions in food processing, increasing partner turnover, and increasing product quality and quantity.